2017
DOI: 10.3389/fcimb.2017.00156
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Clinical Presentation, and Outcome of Acinetobacter baumannii Bacteremia

Abstract: Infections caused by Acinetobacter baumannii (AB), an increasingly prevalent nosocomial pathogen, have been associated with high morbidity and mortality. We conducted this study to analyze the clinical features, outcomes, and factors influencing the survival of patients with AB bacteremia. We retrospectively examined the medical records of all patients developing AB bacteremia during their hospital stay at a tertiary care hospital in Beirut between 2010 and 2015. Ninety episodes of AB bacteremia were documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 26 publications
6
58
1
4
Order By: Relevance
“…We found an association between exposure to steroid therapy and development of MDR-AB infection. This distinguishing feature of MDR-AB infections was recently reported by Ballouz and coworkers (39), but the meaning of this association is not yet understood. Since most of patients with MDR-AB infection had pneumonia (69.6%), it is possible that the link between steroid use and MDR-AB infection might be due to steroid administration in the management of severe pneumonia to reduce inflammation (40).…”
Section: Discussionmentioning
confidence: 54%
“…We found an association between exposure to steroid therapy and development of MDR-AB infection. This distinguishing feature of MDR-AB infections was recently reported by Ballouz and coworkers (39), but the meaning of this association is not yet understood. Since most of patients with MDR-AB infection had pneumonia (69.6%), it is possible that the link between steroid use and MDR-AB infection might be due to steroid administration in the management of severe pneumonia to reduce inflammation (40).…”
Section: Discussionmentioning
confidence: 54%
“…An identical macrorestriction pattern (PFGE-type) was detected in isolates of two different hospitals in 2008 in North Rhine-Westphalia confirming that inter-hospital transmission is possible [26]. Moreover, a prolonged hospital stay is frequently associated with exposure to antibiotics [68]. A. baumannii can rapidly acquire resistance by mutation during antimicrobial therapy [44].…”
Section: The Risk Factors Associated With a Baumannii Infectionsmentioning
confidence: 84%
“…One study, addressing patients with neutropenic fever have found that increased in-hospital mortality rate was associated with the duration of neutropenia and treatment modification for clinical deterioration [26]. Moreover, in concordance with previous worldwide studies, Ballouz et al found that prolonged hospital stay that is often associated with a loss of functionality, as well as antibiotic and steroid exposure especially in critically ill patients, increases the risk of exhibiting A. baumannii bacteremia with poor outcome [27]. Dahdouh et al conducted a study on ninetyfive A. baumannii strains isolated from a tertiary care center in Beirut and showed that their virulence profiles were highly variable and without a specific pattern [28].…”
Section: Acinetobacter Baumannii In Lebanon: a Real Threat Or An Overmentioning
confidence: 63%
“…Few years later, carbapenem resistant Acinetobacter species started to emerge in this same hospital [32] [34]. A study conducted at a major tertiary care center in Beirut showed that the majority (82/90) of A. baumannii isolated from patients with bacteremia were resistant to carbapenem but remained susceptible to tigecycline and colistin [27]. In this study, colistin susceptibility was tested by the Kirby-Bauer technique [27]; this technique is not considered accurate for testing the susceptibility to colistin.…”
Section: Epidemiology Of Carbapenem Resistant Acinetobacter Species Imentioning
confidence: 91%
See 1 more Smart Citation